STRATEGI PEMERINTAH DESA DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI TENGAH PANDEMI COVID-19 DI KANTOR DESA PUSUNGE KECAMATAN TABUKAN UTARA KABUPATEN KEPULAUAN SANGIHE - MOCLIN, ALPRINCES; RORONG, ARIE; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2021)
This study aims to find out how the Village Government Strategy in Improving the Quality of Public Servicesin the Midst of the COVID-19 Pandemic at the Pusunge Village Office, Tabukan Utara District, SangiheIslands Regency. This study used descriptive qualitative method. The theory used in this research is thetheory of strategic indicators from Freed R. David which includes Strategy Formulation, StrategyImplementation, Strategy Assessment. The research informants were the village head, village secretary,hamlet head, health agencies and village communities totaling 7 people. Data collection techniques thatresearchers use are observation, interviews and documentation. The results of this study indicate that thestrategy formulation is more effective, and in implementing the strategy the government has tried to providegood service and it can be judged that the strategies taken by the village government have been realized wellby making existing policies such as making village office guard schedules, providing shelter and alwaysremind 3M (wear masks, wash hands, and maintain distance), although in implementation there are stillobstacles in the form of lack of participation from the community in implementing the strategies taken by thevillage government and still not complying with existing health protocols.Keywords: Strategy, Quality, Public Service, COVID-19 Pandemic